2012
DOI: 10.2967/jnumed.111.097162
|View full text |Cite
|
Sign up to set email alerts
|

Brain and Whole-Body Imaging of Nociceptin/Orphanin FQ Peptide Receptor in Humans Using the PET Ligand 11C-NOP-1A

Abstract: Nociceptin/orphanin FQ peptide (NOP) receptor is a new class of opioid receptor that may play a pathophysiologic role in anxiety and drug abuse and is a potential therapeutic target in these disorders. We previously developed a high-affinity PET ligand, 11C-NOP-1A, which yielded promising results in monkey brain. Here, we assessed the ability of 11C-NOP-1A to quantify NOP receptors in human brain and estimated its radiation safety profile. Methods After intravenous injection of 11C-NOP-1A, 7 healthy subjects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
64
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(75 citation statements)
references
References 27 publications
10
64
0
1
Order By: Relevance
“…Brain autoradiography studies in rodents have revealed a very high concentration of NOP receptors in the frontal cortex, and there are particularly high levels of NOP receptors in the cingulate cortex (Neal et al 1999; Sim and Childers 1997; Sim et al 1996). Consistent with these rodent findings, human positron emission tomography (PET) and post-mortem autoradiography studies have also reported high distribution of NOP receptors in the cingulate cortex and striatum (Berthele et al 2003; Lohith et al 2014; Lohith et al 2012). Moreover, NOP receptors are localized on dopaminergic nuclei in the VTA, and administration of a NOP receptor agonist inhibited dopamine neurotransmission in the VTA and NAc (Koizumi et al 2004a; Koizumi et al 2004b; Murphy et al 1996; Murphy and Maidment 1999; Murphy et al 2004).…”
Section: Discussionsupporting
confidence: 54%
“…Brain autoradiography studies in rodents have revealed a very high concentration of NOP receptors in the frontal cortex, and there are particularly high levels of NOP receptors in the cingulate cortex (Neal et al 1999; Sim and Childers 1997; Sim et al 1996). Consistent with these rodent findings, human positron emission tomography (PET) and post-mortem autoradiography studies have also reported high distribution of NOP receptors in the cingulate cortex and striatum (Berthele et al 2003; Lohith et al 2014; Lohith et al 2012). Moreover, NOP receptors are localized on dopaminergic nuclei in the VTA, and administration of a NOP receptor agonist inhibited dopamine neurotransmission in the VTA and NAc (Koizumi et al 2004a; Koizumi et al 2004b; Murphy et al 1996; Murphy and Maidment 1999; Murphy et al 2004).…”
Section: Discussionsupporting
confidence: 54%
“…We have recently discovered both labeled and unlabeled NOP receptor tracers with subnanomolar binding affinities with no intrinsic activity (i.e., antagonists), high selectivity, CNS penetration, and low nonspecific binding (Pedregal et al, 2012). 5 was safe, with favorable kinetics and reproducibility (Lohith et al, 2012(Lohith et al, , 2014, and exhibited distribution volume (V T ) consistent with known NOP density distribution (Berthele et al, 2003).…”
Section: Introductionmentioning
confidence: 75%
“…Parent fraction was measured by high-performance liquid chromatography (HPLC) to determine the metabolite corrected plasma input function, as previously described in more details (Lohith et al, 2012). Sample chromatogram can be found in (Supplemental Figure 4).…”
Section: Magnetic Resonance Imaging and Pet Image Acquisition Proceduresmentioning
confidence: 99%
“…At a translational level, the use of radiolabeled molecules that bind the NOP receptor in the brain (Hostetler et al, 2013; Kimura et al, 2011; Linz et al, 2014; Lohith et al, 2014; Lohith et al, 2012; Pedregal et al, 2012; Pike et al, 2011; Thomsen et al, 2000) could provide insight into the association between N/OFQ-NOP receptor levels, human learning and memory, and brain disorders (e.g. Posttraumatic stress disorder, Alzheimer, Parkinson, etc.).…”
Section: Nociceptin and The Nociceptin Receptor In Learning And Mementioning
confidence: 99%